If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+6=(2x+6)
We move all terms to the left:
2x+6-((2x+6))=0
We calculate terms in parentheses: -((2x+6)), so:We get rid of parentheses
(2x+6)
We get rid of parentheses
2x+6
Back to the equation:
-(2x+6)
2x-2x-6+6=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 3(x-7)+5=-37 | | X-0.8x=180 | | 2x+6=-2(2x | | 1/5x-7=18 | | 15+5x=64 | | 0.4n+0.1=0.5(n+5) | | d-(-12=16 | | 2.5x-13=8 | | X-3/5=3x-5/5 | | u8-u16=32 | | (18x-8)+(70-4x)=90° | | 4(x-4)÷2=2(x+6)÷111 | | p²+2p=48 | | y/5-1=10 | | 3/2x-1/2(x+8)=1 | | 2-(x-4)=10 | | x-3/2=68 | | X-1.0x=81 | | C=2n+2600 | | 2u+48=10u | | (2-3x)/4=12 | | 2x+(x+1)^1/2=8 | | g+7=|−2| | | 3/8f=17.5 | | 6(5z+3)=45 | | -5c+7+9=29 | | -2(2f+8)=-4(-f+2) | | z2–72=0 | | 3w−2w=9 | | 6-x=4x-12 | | -(2n+6)=3(5-n) | | 7(y−5)=42 |